Development of Tourism Attractiveness of Nagari Canduang Koto Laweh Canduang District, Agam Regency - Sarmiadi; Yosi Suryani; Elni Sumiarti (International ABEC, 2022)
One form of tourism development is the establishment of many tourist villages, including those in Nagari Canduang Koto Laweh, Canduang District, Agam Regency. This study aims to identify tourist attractions in Canduang Koto Laweh Tourism Village, Agam Regency and their development strategies. This study uses a qualitative descriptive approach using primary data obtained through observation and interviews with relevant stakeholders. Secondary data is collected through supporting sources and references and data analysis using an interactive model method. The results of this study indicate that Nagari Canduang, City of Laweh has a lot of tourism potential both from the aspect of natural tourism, cultural tourism and artificial tourism. However, this potential has not been developed properly so that the number of tourist visits has not increased. For this reason, it is recommended that a massive promotion be carried out to stakeholders.